The Transformation of Administrative Law Through Legal Transfers: The Case of Government Agencies in Post-1989 Poland - Bieś-Srokosz, Paulina (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The transformations of the Polish legal system after 1989, in particular administrative law, were dictated by external and internal changes. The Polish legislator, in making changes in the legal order, tried to respond to the growing needs of society. In some cases, he has made use of ready-made legal solutions of foreign legal systems. In this case, we talk about government agencies that have been transplanted from the German legal system.
Keywords: przeszczepy legalne; agencje rządowe RP; prawo administracyjne